The Mechanisms of Space Formation in Contemporary Theater – The Play Days of Madness and Honey as a Model (Al-Academy, 2026)
Contemporary theater has witnessed major transformations at the level of the performance industry as well as the mechanisms of work, so experimentation, innovation, and deviation from traditional patterns were the prominent feature in the experiences of most theater directors, which included all the elements included in the show, foremost of which is space. This led to the diversity of experiences as well as innovations, which expanded the mechanisms of work and changed their artistic and aesthetic requirements as a result of technical and artistic transformations, which in turn rebuilt the aesthetic and semantic relationship between The elements involved in the construction of the theatrical performance. Accordingly, this research delves into understanding and studying the mechanisms followed by directors in painting and shaping space in contemporary theater, as the researcher divided his research into four chapters, the first of which dealt with the research problem (the methodological framework), which he identified with the following question: (What are the mechanisms used by the contemporary theater director in formulating and shaping his theatrical space?As for the importance of the research, the researcher identified the directors and students of theater art as the most prominent beneficiaries, while the goal of the research is to identify the mechanisms of space formation in contemporary theater, and then the researcher set limits for the research and define the terms and define them procedurally. The second chapter (Theoretical Framework), which included two researches, dealt in the first (the specificity of space in contemporary theater) with the specific variables that drew the form of contemporary space, and the most important elements that constituted it, while in the second (The construction of space in contemporary theater) is the most important innovations of directors in space, and then he identified the most important indicators that resulted from the theoretical framework, most notably: space in the context of contemporary directing has a special characteristic of being flexible, open to all possibilities of work, as it is not determined by a specific place or time as much as it is related to the directorial vision. While the third chapter dealt with (research procedures), which included (the research community, the method of selecting the sample, the research methodology, the means of measurement, and the analysis of the sample, which was represented by the presentation of the days of madness and honey), while the fourth chapter (results and conclusions) included the most important results of the research, the most prominent of which were: (The director employed space as an effective semantic element, not just as an incubator work space for the dramatic act, but he also employed space to direct the project's paths in order to ensure the achievement of his aesthetic narratives.Then he reviewed the most important conclusions he reached, the most important of which are: (The transformation of space in contemporary theater from being a space to contain the act to an active semantic and aesthetic element that contributes to the production of meaning and pushes the recipient to a plurality of reading, which enhanced his expressive energy), and then the researcher reviewed the list of sources he used in his research.